Antecedents of School Teacher's Turnover Intention - Hendri Eka Jaya Putra; Yohana F. Cahya Palupi Meilani; Albert Surya Wanasida (Budapest International Research and Critics University, 2022)
This study aims to analyze what factors influence the turnover intention of teachers in private schools. The type of research used is library research with a descriptive approach. Sources of data from secondary data and data collection techniques using sources from various reference books and journal articles. To obtain correct and precise results in analyzing the data, the author uses content analysis techniques. The results of the study found that the turnover intention of private school teachers was influenced by factors: young age, gender, shorter tenure, organizational culture, leadership style, compensation, job satisfaction, work motivation, career development, job insecurity, employee relations, opportunities career, salary, benefits and bonuses (compensation), task and job design, working conditions and work responsibilities, organizational commitment and social integration, formal communication, employee centralization, work routines that tend to burnout, redundant roles or tasks, opportunities promotion and career development, general training, supervisor support, peer support, and fair distribution, management style, job mismatch, scheduling/flexibility.